Progress in Shopping Tourism. (8th April 2016) - Choi, Mi Ju; Heo, Cindy Yoonjoung; Law, Rob
ABSTRACT: Shopping has become a main tourist activity and accounts for a considerable amount of tourism expenditure. Previous research has found that shopping tourists stay longer at a destination and spend approximately three to four times more than leisure tourists. However, only a few studies have considered the value of shopping as a primary motivation for travel, and those that did have approached the topic with a limited focus. Against this background, the existing body of research should be examined. Therefore, this study assesses the progress in shopping tourism research to identify trends and propose future research directions.